(E)-β-caryophyllene functions as a host location signal for the rice white-backed planthopper Sogatella furcifera. (July 2015) - Wang, Qi; Xin, Zhaojun; Li, Jiancai; Hu, Lingfei; Lou, Yonggen; Lu, Jing
Abstract: Terpenoids are well known to mediate interactions among plants, herbivores and their natural enemies. In rice, ( E )-β-caryophyllene has been reported to attract a major insect pest, Nilaparvata lugens, and its egg parasitoid, Anagrus nilaparvatae . Yet, it remains unclear whether ( E )-β-caryophyllene also influences other herbivores in rice. Here we demonstrated that a rice ( E )-β-caryophyllene synthase, OsCAS, localizes in cytoplasm and that its transcript was up-regulated following mechanical wounding, the infestation of the rice striped stem borer (SSB) Chilo suppressalis and treatment with jasmonic acid. We also revealed that the rice white-backed planthopper Sogatella furcifera preferred feeding and ovipositing on wild-type (WT) plants over feeding on mutants with low levels of ( E )-β-caryophyllene. The results indicate that ( E )-β-caryophyllene may function as an important signal by which herbivores on rice locate their host. Highlights: OsCAS localizes in cytoplasm. OsCAS transcript was up-regulated by wounding, herbivory and JA treatment. ( E )-β-caryophyllene functions as a host location signal for Sogatella furcifera .